NAVIGATING PRIVACY BOUNDARIES BY INTERNATIONAL ONLINE GAMING PLAYERS - Sofiari Ananda; Nur Fitriyani Saputri (OPINI: Journal of Communication and Social Science, 2025)
This article examines how international online gaming players navigate privacy boundaries in digital interaction, with particular attention to intimacy negotiation across cultural contexts. Using participant observation and autoethnography, the researcher immersed as a player in multiplayer games, joined guilds, and conducted interviews via in-game chat and external platforms. Findings reveal that privacy boundaries are managed through layered self- disclosure, reliance on game affordances such as guild and party systems, and the strategic migration of communication to platforms like Discord and WhatsApp. Cross-cultural differences are also evident: Indonesian players tended to be more cautious and gradual in disclosure, while Western players were more direct in revealing personal information. The study contributes to Communication Privacy Management (CPM) scholarship by highlighting the role of intercultural dynamics in digital intimacy and underscores the fragility of online relationships, which can be both rapidly formed and easily dissolved.